Analysis Of The Determination Of Innovative Work Behavior In Millennial Generation Employees - Pebianti, Vina; Hamdani, Fajri; Juwita, Tia Permata; Panjaitan, David (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This research aimed to investigate how learning agility and organizational culture affect innovative work behavior among millennial employees, with work engagement serving as a mediating variable. A quantitative research design was employed, involving 150 participants selected using a quota sampling method. The data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The findings revealed that learning agility significantly contributes to innovative work behavior, both directly and indirectly through its influence on work engagement. Conversely, organizational culture does not directly impact innovative behavior, though it does influence employees' engagement at work. Furthermore, the study confirms that work engagement mediates the link between learning agility and innovative behavior, whereas no mediating effect was found between organizational culture and innovative behavior. In summary, these findings suggest that personal attributes, particularly learning capability and engagement level, play a more prominent role in shaping innovative behavior among millennials in the workplace.